Aligning Carbon Markets With Sustainable Development Goals in the Least Developed Countries - United Nations Conference on Trade; Development (United Nations, 2024)
Carbon trading under Article 6 of the Paris Agreement presents opportunities and risks for the least developed countries (LDCs). Rather than participating in carbon markets in an ad-hoc fashion, LDCs should build a policy framework that integrates carbon trading into existing development policy and climate policy strategies. The international community can support LDCs through enhanced capacity-building and by strengthening the integrity of carbon markets. This policy brief outlines key benefits, challenges, and policy recommendations for LDCs and development partners to mitigate risks associated with carbon trading under Article 6 and ensure that carbon markets support sustainable development in LDCs.